Estimating the relationship between public and private inputs for K-12 education: Evidence from longitudinal microdata - Philip Vinson (Review of Economic Analysis (REA), 2024)
I examine whether private education expenditures and public K-12 funding are substitutes or complements for households whose children attend public school. Using a longitudinal microdata set, the Panel Study of Income Dynamics, I estimate the response of private household expenditures on education in response to changes in public expenditures. This paper implements a fixed-effects model that controls for unobservable household characteristics. I find evidence of complementarity between public and private education spending with an average elasticity of 2.4.
Keywords: D1; E24; H3; I2; J24; 330; education expenditures; consumption; human capital; public economics